The Resilient Generation of UIN Malang Mathematics Education: Perspective on the Cognitive Load of Students - Ilmi, Ilham Imtiyazil; Aprillia, Yustika Berlian Cindy; Mukti, Taufiq Satria (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
Deep learning needs to be applied in learning, so that the learning process is not limited to cognitive aspects alone. Moreover, the cognitive load that humans can accept is limited. This load does not only come from within the classroom during learning, but also from other factors such as emotions, time constraints, and existing tasks. Cognitive load theory needs to be applied to deal with this, so that the learning portion is in accordance with the conditions required by students. This study conducted on first-semester students of the Mathematics Education study program at UIN Malang aims to identify and analyze existing cognitive load. The study used a quantitative approach with 54 students as sample respondents. Data were collected through a semi-structured guided questionnaire covering aspects of intrinsic load, extraneous load, emotional load, time and task load, and resource load. Data analysis used descriptive statistics with Rasch Model validity testing. The results showed that cognitive load was in the moderate to high category, with intrinsic load, extraneous load, emotional load, time load, and task load in the moderate category, and resource load in the high category. These findings indicate that students are able to manage their cognitive load quite well. However, the high time and task load needs to be addressed as it has the potential to cause cognitive fatigue and reduce learning effectiveness. This study recommends the development of OBE-based adaptive learning strategies that take into account the balance between academic activities and dormitory life.